APPLICATIONS IN THE CLASSROOM: HARDLY ELEMENTARY — FRONTIERS FOR FRESHMAN COMPOSITION WITH CONAN DOYLE’S A STUDY IN SCARLET - Donley, Kate M. (Dialogue, 2(1), 2015)
Three recent television and film adaptations testify to the continuing popularity of Arthur Conan Doyle’s consulting detective Sherlock Holmes. The fast-paced novella that introduces detective duo Holmes and Watson, A Study in Scarlet involves some astonishing elements, and not just in the plot. With just a little probing, collegiate readers may wonder whether Conan Doyle plagiarized his most famous character, invented forensic science, despised Mormons, and accidentally wrote a Western. The novel was adapted as A Study in Pink, the first episode of the BBC’s series Sherlock created by Steven Moffat and Mark Gatiss. Their vision of Holmes set in present-day London will thrill students and also leave them wondering what happened to the second half of the novel. Beyond the predictable (yet exciting) classroom discussion topic of adaptation, A Study in Scarlet presents a rich context for research and discussion by challenging students’ modern-day notions of genre, historical truth, political correctness, and academic credibility. Although this novel is well-suited for high-level secondary or freshman composition classes, advanced students of English literature will find much to explore. This book analysis contains a summary of A Study in Scarlet with explication of its literary features and associated pedagogical issues for the freshman composition class. Topics for more advanced students are also identified. Instructors can make a free virtual casebook of ancillary readings with the Internet links provided. Keywords: college composition, first-year writing, freshman composition, Arthur Conan Doyle, Sherlock Holmes, A Study in Scarlet, detective fiction, adaptation, pseudo-scholarship, fanfiction
Keywords: Type of access: Open Access